2018
DOI: 10.1016/j.ajoc.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Acute macular neuroretinopathy associated with influenza vaccination with decreased flow at the deep capillary plexus on OCT angiography

Abstract: PurposeWe report a case of acute macular neuroretinopathy (AMN) following routine annual inactivated influenza vaccination. Projection-resolved optical coherence tomography angiography (PR-OCTA) was used to analyze the retinal capillary flow within the AMN lesion.ObservationsOur patient reported visual symptoms of her right eye nine days after routine annual influenza vaccination. Multimodal imaging revealed small vessel peripheral vasculitis and AMN in the affected eye. Infectious, immunologic, and hypercoagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…Recently, Liu et al [20] described a case of a middle age woman with OCT features similar to the one we found, but that patient underwent an influenza vaccination and was affected by Raynaud disease, in contrast to our young patient. On the other hand, Introini et al suggested an association between the AMN and the intranasal cocaine use in a 24-year-old woman.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Recently, Liu et al [20] described a case of a middle age woman with OCT features similar to the one we found, but that patient underwent an influenza vaccination and was affected by Raynaud disease, in contrast to our young patient. On the other hand, Introini et al suggested an association between the AMN and the intranasal cocaine use in a 24-year-old woman.…”
Section: Discussionsupporting
confidence: 66%
“…The etiology is still unknown [1]. To date, over 100 cases of AMN have been published and Bhavsar et al in a review reported that 47.5% of described cases were associated with a non-specific flu-like illness or fever [2], but to date a strong link with the influenza virus has not been yet demonstrated [20]. One documented association was with the dengue fever [11,21].…”
Section: Discussionmentioning
confidence: 99%
“…We applied a projection-resolved (PR-OCTA) algorithm in postprocessing to reduce projection artifacts from superficial vessels projected onto the deeper capillary layers and to reduce projection artifacts within hyperreflective lesions. We implemented a version of the PR-OCTA algorithm developed by Zhang et al 12 , 16 , 17 These authors noted that projection tail artifacts in OCTA have lower decorrelation values compared to real vessels. 17 , 20 Taking advantage of this observation, the algorithm searches each A-scan for successive, high-valued peaks, which correspond to real vessels.…”
Section: Methodsmentioning
confidence: 99%
“…PAMM has been associated with reduced blood flow of the SCP and DCP, 2 MCP alone, 7 or MCP and DCP. 1 , 5 , 9 11 Similarly, AMN has been associated with occlusion of the DCP 4 , 12 or choriocapillaris. 13 , 14 The two major confounding factors in all these studies are projection artifacts cast from superficial blood vessels onto the deeper layers, and artifactual OCT signal attenuation underneath INL/ONL hyperreflective lesions.…”
mentioning
confidence: 99%
See 1 more Smart Citation